The influence of recent developments in EU procurement law on the procurement regulation of member states: a case study of the UK, the Netherlands and France - De Mars, Sylvia (2011)
Since 1993, the European Union has dramatically increased the scope and volume of its procurement regulation; particular increases have been made in terms of the procurement procedures made available, and the obligations that national contracting authorities have in light of EU law. This thesis examines the influence that recent developments in EU public procurement law have had on national procurement regulation in the UK, the Netherlands, and France.